Stabilization effect and mechanism of heavy metals by microbial consortium of phosphate-solubilizing bacteria and urease-producing bacteria - Zhu, Xuezhe; Zhou, Yupin; Yan, Zhenghao; Yan, Yongfang; Li, Shuangquan; Yu, Mingjiao; Yan, Xiao; Zhang, Mingjiang (Frontiers in Microbiology, 2025)
IntroductionStabilization of heavy metals through phosphate-solubilizing bacteria (PSB) induced phosphate precipitation and urease-producing bacteria (UPB) induced carbonate precipitation are promising bioremediation methods. However, little attention has been conducted on the combined action of the above two bioremediations to stabilize heavy metals.MethodsPSB and UPB were isolated from the environment and their growth characteristics and antagonistic properties were studied. A simulated solution of acidic leachate was prepared based on heavy metal contaminated soil. Microbial consortium of PSB and UPB were constructed for the stabilization of heavy metals by optimizing carbon and nitrogen sources. The microstructural and compositional changes during the biostabilization process were more deeply analyzed using XRD, FT-IR and SEM-EDS.Results and discussionThe precipitation of heavy metals could be promoted effectively when soluble starch (10.2 g/L) was used as carbon source and urea (7.8 g/L) as nitrogen source. The stabilization rates for Cu, Zn, Cd, and Pb were 98.35, 99.78, 99.09, and 92.26%, respectively. The stabilization rates of the combined action of PSB and UPB were significantly higher than that of the two microorganisms alone. An in-depth analysis showed that the composite metals were precipitated as dense precipitate encased in carbonate and phosphate, and additionally could be stabilized in the form of biosorption. Finally, the stabilization mechanism of heavy metals based on biomineralization and biosorption is proposed. These findings provide new theoretical support for sustainable remediation and management strategies for composite heavy metal polluted areas.